Illness stage and predominant polarity in bipolar disorder: Correlation with burden of illness and moderation of treatment outcome. (August 2021) - Kamali, Masoud; Pegg, Samantha; Janos, Jessica A.; Bobo, William V.; Brody, Benjamin; Gao, Keming; Ketter, Terence A.; McElroy, Susan L.; McInnis, Melvin G.; Rabideau, Dustin J.; Reilly-Harrington, Noreen A.; Shelton, Richard C.; et al.
Abstract: Bipolar disorder often follows a set progression best described in stages where advanced stages are associated with poorer outcomes. Bipolar disorder is also often characterized by a predominance of episode polarity, where some individuals experience more depressive episodes (termed predominant depressive polarity) while others experience more hypo/manic episodes (termed predominant hypo/manic polarity). We examined the associations between staging and predominant polarity with measures of illness burden and treatment outcome utilizing data from a six-month comparative effectiveness trial of lithium and quetiapine in bipolar disorder (Bipolar CHOICE). We used number of self-reported lifetime mood (depressive and hypo/manic) episodes as a proxy for staging and ratio of depressive to manic episodes to define predominant polarity. Polarity and staging were correlated with several measures of burden of illness. Childhood abuse was correlated with more lifetime mood episodes, while more depressive episodes and depressive polarity were correlated with more anxiety disorder comorbidity. Depressive polarity was also correlated with more past trials of psychotropics, particularly antidepressants. However, neither staging nor predominant polarity moderated the randomized treatment effect of lithium vs. quetiapine. Number of depressive episodes in the past year was identified as a potential predictor of overall worse treatment outcome, regardless of medication condition. In conclusion, though staging and predominant episode polarity correlated with several measures of illness burden, they were not associated with differential treatment outcomes. This could be because many of our patients presented for treatment at advanced stages of illness and further highlights the need for early intervention in bipolar disorder.